KAJIAN YURIDIS TERHADAP TINDAK PIDANA KORUPSI - M.H, Ismail (IAIN Langsa, 2017)
Corruption in Indonesia is so severe as social diseases, reinforced by corrupt practices exposed by the media increasing perceptions of corruption are like illness especially at the end of the New Order era even on the current reform order, almost everywhere. Starting from small officials to high officials. The results of the study indicate an important assertion, because the financial loss of the state is one of the essential elements of corruption in addition to unlawful acts. Thus, the criminal act of corruption is not abolished even then the element of state loss is not proven in court because it has been returned by the suspect, seizure of a number of goods. Barriers at investigation level, juridical investigators remain guided by KUHAP and applicable legislation, investigators lack understanding of the meaning of substance in UUPTPK especially in understanding the element